PENGARUH MINAT MAHASISWA TERHADAP ONLINE SHOP DALAM PERKEMBANGAN PRODUK HALAL - Nanda Fajariah; Nahar Alang Abdul Ghani (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
This research is motivated by the assumption that student interest will greatly affect a business or online shop when a business or online shop they use provides good service and provides satisfaction to consumers by providing information about the product being halal. But in reality there are still many online shops that do not provide good service to consumers, from those who provide damaged products to fraud. This research was conducted in the department of Islamic economics, Faculty of Islamic Religion, Islamic University of North Sumatra. The population is 100 people, the sample is taken by accidental sampling, namely the technique of determining the sample based on chance if it is considered that the person who happened to be met is suitable as a data source, totaling 30 students. Data collection techniques through observation, interviews, questionnaires, and documentation. The researcher analyzed the data by using quantitative descriptive method by conducting statistical tests. To analyze the data, the researcher used research instrument test, classical assumption test and hypothesis test. From the results of this study, it was found that the relationship between student interest in online shops, which was strong. This means that the contribution given by the student interest variable to the online shop is valid while the remainng is influenced by other variables that are not in this study. And a review of the development of halal products regarding the online shop variable is appropriate, because based on the verse of the Qur'an QS Al-Mutaffifin/83:1-3, the buyer conducts buying and selling (commerce) with the online shop on a consensual basis, also has a contract agreed upon in the agreement. beginning. And achieve the target of customer satisfaction.